EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN HORTIKULTURA DI LAHAN SEKOLAH TINGGI THEOLOGIA MALUKU DUSUN KATE-KATE DESA HUNUTH KECAMATAN TELUK AMBON - Meilany Lesnussa; Elisa J Gaspersz; Rudy Soplanit (Universitas Pattimura, 2017)
The study was conducted from October to November 2016 in Maluku Theology School Yard in Kate-Kate, Hunuth Village, Teluk Ambon Sub District with 11.7 ha area. The study was conducted with the objectives for: 1) obtaining data on the physical condition of the land in the research area as the basic material in assessing the suitability of the land for horticultural crops; 2) knowing the limiting factors present in the field and can be proposed for improvement; 3) determining the land for appropriate horticultural crops. The research method was survey method with distance of transect observation. Based on the results of field observation and land evaluation, it showed that: 1) the physical condition of the land in the research area was low hilly area with the soil type of Cambisol and land cover in the form of settlements, mixed plants and shrubs, 2) Based on the results of land evaluation there were 3 main limiting factors, such as rainfall, erosion and slope, 3) Based on actual suitability, the most suitable plants to recommend for each land unit were duku and rambutan.